Is Drosophila song amplitude structure a communication signal? - Brüggemeier, B; Goodwin, S (2017)
Drosophila courtship song has been studied for over 60 years and remains an area of active research today. Several studies have investigated the physiological mechanisms for fly song production, but no unifying account exists. We review fly song production and integrate published data to a mathematical model of courtship song production. We hypothesize that muscle dynamics underlie fluctuations in the amplitude of courtship song. Our model suggests that these fluctuations can be measured and we introduce the term 'song amplitude structure' (SAS) for those measurements. We predict that SAS signals muscle power and we validate our prediction in muscle mutants of the Drosophila myosin light chain (Dmlc2) gene. We then investigate whether SAS is a communication signal in Drosophila. We show that the two species D. melanogaster and D. simulans differ in their SAS and that both females and males behaviourally discriminate their species SAS from other SAS. This suggests that SAS is a communication signal in Drosophila. Perception of SAS may be affected by noise and we therefore examine the effect of noise on responses to SAS. We find that female auditory responses are not impaired by noise in SAS, however male auditory responses are impaired by noise in SAS. This suggests that males and females may be processing noise in SAS differently. Future work should investigate whether sexually dimorphic auditory neurons respond differently to noise in SAS. We hope that our work will be helpful for investigating fluctuations in amplitude of fly song. We also wish that researchers can use our work for studying the mechanisms underlying both the production of SAS and the perception of SAS.